The Tradition Of Reading Shalawat Diba' On Friday Night At Nurusshaleh Islamic Boarding School, East Katol Village, Kokop Bangkalan - Nisa, Sofia Hoirotun; Mas’ud, Mas’ud; Nafsiyah, Fitrotun; Alon, Frances; Dylan, Moatti (Journal International Dakwah and Communication, 2021)
In this study, we will discuss a tradition in the study of living hadith, namely the tradition of reading shalawat diba' on Friday night at the Nurusshaleh Islamic Boarding School, East Katol Village, Kokop District, Bangkalan Regency. From the results of research conducted by researchers, it can be concluded that shalawat is a form of praise, flattery, and prayer addressed to the Prophet Saw as evidence of our respect, love and gratitude to him. At Pondok Pesantren Nurusshaleh Katol Timur Kokop Bangkalan the recitation of shalawat diba' has become a tradition every Friday night. This started because of the lack of religious knowledge of the community in East Katol Village. So for them the recitation of shalawat diba' is something foreign. Then KH. Abdullah Nawawi applies to read shalawat diba' once a week at the Nurusshaleh Islamic Boarding School so that they know and can practice in their respective environments